PENGARUH KEPEMIMPINAN DAN PENGALAMAN KERJA TERHADAP MOTIVASI KERJA DAN PRODUKTIVITAS KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V PABRIK KELAPA SAWIT (PKS) KEBUN TERANTAM - Lia Winda Sari Lubis; Susi Hendriani; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted at PT. Perkebunan Nusantara V Palm Oil Factory Kebun Terantam. The purpose of this study is to determine the effect of leadership variables and work experience on work motivation and employee productivity at PT. Perkebunan Nusantara V Palm Oil Factory Kebun Terantam. The study population was 185 people and the research sample was taken using random sampling. Determination of sample in this research done by using slovin formula, hence obtained amount of sampel counted 65 people.The research variables used were leadership, work experience of independent variable and work motivation, work productivity as dependent variable. Data analysis method used is descriptive analysis and multiple regression analysis of two stages by using program SPSS 22 for windows.The results of this study concluded that in the first stage of leadership variables and work experience partially or simultaneously have a significant effect on work motivation as well as in the second stage of work motivation has a significant effect on work productivity. The result of calculation of coefficient of determination (R2 ) of first stage is equal to 0,569 which mean, leadership variable and work experience can explain work motivation variable equal to 56,9%, while the rest equal to 43,1% influenced by other variable not examined in this research . And the second determination coefficient (R2 ) is 0,579 which means, work motivation variable can explain work productivity variable equal to 5,79%, while the rest equal to 42,1% influenced by other variables not examined in this research.Key Words : Leadership, Work Experience, Work Motivation, and Work Productivity